2001
DOI: 10.1074/jbc.m103385200
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone-deficient Period Prior to the Onset of Hearing Is Associated with Reduced Levels of β-Tectorin Protein in the Tectorial Membrane

Abstract: The genes for ␣-and ␤-tectorin encode the major noncollagenous proteins of the tectorial membrane. Recently, a targeted deletion of the mouse ␣-tectorin gene was found to cause loss of cochlear sensitivity (1). Here we describe that mRNA levels for ␤-tectorin, but not ␣-tectorin, are significantly reduced in the cochlear epithelium under constant hypothyroid conditions and that levels of ␤-tectorin protein in the tectorial membrane are lower. A delay in the onset of thyroid hormone supply prior to onset of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 47 publications
(61 reference statements)
3
53
0
Order By: Relevance
“…For example, in α-tectorindeficient mice, although affected animals are insensitive to tonal stimulation, frequency tuning remains sharp even though the TM is detached from the spiral limbus according to Legan et al (2000). In the case of β-tectorin-deficient mice, although the second, lowfrequency resonance reported by Legan et al (2000) was not observed, Russell et al (2007) reported that high-frequency tuning sharpness is actually enhanced at CF relative to normal animals even though the TM is enlarged and exhibits the disrupted striated-sheet matrix described previously in hypothyroid rats that also exhibit reduced levels of β-tectorin (Knipper et al 2001). While it is important to replicate these findings and to determine if they generalize to other models, these data generally suggest that the link between TM structure and composition and the sharpness of tuning may be more complex than previously thought.…”
Section: Fig 4 Comparisons Of Adult Valuesmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, in α-tectorindeficient mice, although affected animals are insensitive to tonal stimulation, frequency tuning remains sharp even though the TM is detached from the spiral limbus according to Legan et al (2000). In the case of β-tectorin-deficient mice, although the second, lowfrequency resonance reported by Legan et al (2000) was not observed, Russell et al (2007) reported that high-frequency tuning sharpness is actually enhanced at CF relative to normal animals even though the TM is enlarged and exhibits the disrupted striated-sheet matrix described previously in hypothyroid rats that also exhibit reduced levels of β-tectorin (Knipper et al 2001). While it is important to replicate these findings and to determine if they generalize to other models, these data generally suggest that the link between TM structure and composition and the sharpness of tuning may be more complex than previously thought.…”
Section: Fig 4 Comparisons Of Adult Valuesmentioning
confidence: 94%
“…While many inner and middle ear anomalies have been reported in hypothyroid animals, the most commonly and consistently reported defects are limited to those associated with the tectorial membrane (TM) and cochlear innervation (Deol 1973, 1976; Anniko and Rosenkvist 1982;Uziel et al 1981Uziel et al , 1983aUziel et al , b, 1985Remezal and Gil-Loyzaga 1993;Rusch et al 2001;Knipper et al 2001;Griffith et al 2002;Christ et al 2004;Johnson et al 2007). Of these, the TM has received the greatest amount of attention as a prospective source of pathology, in part, no doubt, because of its imposing presence and distorted character, as shown in histological section under some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Data from models of severe and prolonged hypothyroidism have established a catalog of events in the developing cochlea, brain, and bone that depend on thyroid hormone. This catalog includes opening of the tunnel in the organ of Corti of the cochlea at P5-P8 (18,49), shaping of the tectorial membrane in the cochlea through the expression of the tectorial membrane-specific proteins ␣-tectorin (coded by the gene Tecta) and ␤-tectorin (coded by the gene Tectb) (31,45), arrival of efferent innervation at cochlear outer hair cells (12,60), expression of the neuron-specific gene synaptotagmin Srg1 (20,44), and the maturation and mineralization of bone-forming chondrocytes and mesenchymal cells (1,52). The cochlea controls T3 levels locally through the expression of two deiodinases, Dio2 and Dio3, and is therefore somewhat independent of circulating levels of T3 if sufficient amounts of T4 are provided (11,39).…”
mentioning
confidence: 99%
“…Western Blot analysis from cochlea tissue was performed as described (24). The specifity of the KCNQ4 antibody was verified by preadsorbing the antibody with the antigenic peptide.…”
mentioning
confidence: 99%